2023
DOI: 10.1177/03331024221128278
|View full text |Cite
|
Sign up to set email alerts
|

Functional magnetic resonance imaging in migraine: A systematic review

Abstract: Background Migraine is a highly prevalent primary headache disorder. Despite a high burden of disease, key disease mechanisms are not entirely understood. Functional magnetic resonance imaging is an imaging method using the blood-oxygen-level-dependent signal, which has been increasingly used in migraine research over recent years. This systematic review summarizes recent findings employing functional magnetic resonance imaging for the investigation of migraine. Methods We conducted a systematic search and sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 178 publications
(472 reference statements)
0
15
0
Order By: Relevance
“…MRI studies have reported inconsistent differences between individuals with migraine and healthy controls [ 7 ]. Structural MRI studies have reported abnormalities such as white matter hyperintensities and volumetric changes in individuals with migraine [ 54 ], while fMRI studies have suggested changes in pain-processing and visual networks [ 55 57 ]. Reasons for the failure to consistently replicate these findings may include insufficient sample sizes, heterogeneous populations, and differences in analytical approaches [ 54 , 55 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI studies have reported inconsistent differences between individuals with migraine and healthy controls [ 7 ]. Structural MRI studies have reported abnormalities such as white matter hyperintensities and volumetric changes in individuals with migraine [ 54 ], while fMRI studies have suggested changes in pain-processing and visual networks [ 55 57 ]. Reasons for the failure to consistently replicate these findings may include insufficient sample sizes, heterogeneous populations, and differences in analytical approaches [ 54 , 55 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Structural MRI studies have reported abnormalities such as white matter hyperintensities and volumetric changes in individuals with migraine [ 54 ], while fMRI studies have suggested changes in pain-processing and visual networks [ 55 57 ]. Reasons for the failure to consistently replicate these findings may include insufficient sample sizes, heterogeneous populations, and differences in analytical approaches [ 54 , 55 , 57 ]. Few fMRI studies have explored the efficacy predictors of mAbs against CGRP signaling, or erenumab-induced biomarker changes.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, patients with less frequent use of symptomatics after galcanezumab therapy improved more evidently in global efficiency. These correlations, although not exhaustive regarding a direct effect of CGRP inhibition in normalizing cortical networking, could support the hypothesis that an efficient and specific antinociception, whenever wielded in the periphery, could potentially act on the complex brain dysfunctions predisposing to attack onset (4,31).…”
Section: Correlation With Clinical Efficacymentioning
confidence: 76%
“…14 A dural inflammatory theory poses that the vasoactive neurotransmitters released by dural stimulation cause neurogenic inflammation and secondary vasodilatation, 15 but this mechanism is not supported by the fact that nonvasoconstricting inhibitors of neurogenic inflammation have not been effective in the treatment of migraine 16 and that longitudinal structural imaging has never detected the consequences of repeated dural inflammation. 17 In recent years, a primarily neural theory has been supported by functional imaging studies during migraine, which have consistently demonstrated activation of central brain areas, including the brainstem in both spontaneous and triggered migraine, 18 as well as early functional imaging changes before pain onset, suggesting that attack initiation must occur centrally. 6 An intact blood-brain barrier has been suggested on imaging during migraine attacks, 19 so dural changes that could be the source of headache are unlikely to be the first process in the migraine attack.…”
Section: Migraine Neuroanatomymentioning
confidence: 99%
“…In recent years, a primarily neural theory has been supported by functional imaging studies during migraine, which have consistently demonstrated activation of central brain areas, including the brainstem in both spontaneous and triggered migraine, 18 as well as early functional imaging changes before pain onset, suggesting that attack initiation must occur centrally 6 . An intact blood-brain barrier has been suggested on imaging during migraine attacks, 19 so dural changes that could be the source of headache are unlikely to be the first process in the migraine attack.…”
Section: Migraine Neuroanatomymentioning
confidence: 99%